Badania satysfakcji pracowników na przykładzie Volkswagen Motor Polska - Bilińska, Joanna (Employee Satisfaction Surveys on the Example of Volkswagen Motor Polska, 2008)
In the modern European organizations, the employee satisfaction surveys belong already to the conventional standards of Human Resources Management. It is enough to mention that regular, systematized analyzing of employees' satisfaction and motivation level constitutes one of the key factors of the EFQM Excellence Model in criteria devoted to the employees. However, despite the commonly shared view, that it is valuable to know opinions of the workers about the company, enterprises that decide to implement opinion surveys tend to face many difficulties. Answers given to the questions of questionnaires can serve as a barometer to measure the general mood of the employees, validity of the implemented personnel policy, information flow in the enterprise or competence of the managerial staff. Like the main purpose of the survey, also the acceptable level of openness by giving feedback to the employees, and views of improvement measures to be taken in response to the identified weaknesses of the organization, are disputable. This paper is supposed to present the approach to the process of employee satisfaction surveys based on solutions elaborated in Volkswagen Motor Polska. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 509-522